Antarctobius bidentatus Champion 1918 - Posadas, Paula (Zenodo, 2008)
Antarctobius bidentatus (Champion 1918) Hypera bidentata Champion 1918: 176; Listroderes bidentatus Kuschel 1955: 289 ( Listroderes subgenus Antarctobius ); Morrone 1992a: 6 ( Antarctobius ). Published as part of Posadas, Paula, 2008, A preliminar overview of species composition and geographical distribution of Malvinian weevils (Insecta: Coleoptera: Curculionidae), pp. 1-26 in Zootaxa 1704 on page 13, DOI: 10.5281/zenodo.180856